UPAYA HUKUM BAGI PIHAK YANG MENOLAK PUTUSAN ARBITRASE AD-HOC - Mirza, Farrah Rizky Amelia (Faculty of Law, University of Palembang, 2019)
Dispute resolution through alternative channels is arbitration known since the conflict with Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Arbitration is a method of civil approval outside the general court made based on an arbitration agreement made by the parties to the dispute. Ad-hoc arbitration is an arbitration specifically designed to resolve or reduce certain disputes, or in other words, ad-hoc arbitration is incidental. Arbitration decisions can be returned if it is agreed to contain no-no in Article 70 letter (a), (b), (c) Law Number 30 Year 1999. Can be proven by one of the disadvantaged parties, it can be asked. Cancellation to the Chair of the District Court and being received by the Chair of the Supreme Court requesting an examination of the cancellation of the arbitration award at the first and last level. The Judicial Review (PK) can also be used in arbitration disputes that have permanent legal requirements, asking PK to be asked to the Supreme Court, which is submitted requesting PK to approve the arbitration decision, will be the decision of the Chair of the District Court to support the cancellation of the award.